Dermatovenereology of Russian Federation in 2020: Working Under a Pandemic - Alexey A. Kubanov; Elena V. Bogdanova (Vestnik Dermatologii i Venerologii, 2021)
The article presents an analysis of the resources and activities of medical organizations providing medical care in the field of dermatovenereology for the period 20152020. Up-to-date data on the number of medical organizations and units providing specialized medical care in the field of dermatovenereology are provided. A description of the main changes in the provision of the population of the Russian Federation with dermatovenereologists, staffing with dermatovenereologists of medical organizations is given. Changes in the number of outpatient visits in 2020 are given. The dynamics of the bed fund of 24-hour and day hospitals of a dermatovenereological profile, the bed occupancy, the number of patients treated is described. The data on the incidence of sexually transmitted infections, infectious skin diseases are presented. Prevalence and incidence rates of diseases of the skin and subcutaneous tissue, including atopic dermatitis and psoriasis, are given. The impact of measures aimed at preventing the spread of a new coronavirus infection and organizing the provision of medical care to patients with COVID-19 on the performance rates of dermatovenereologic medical organizations has been demonstrated.